Answer:
f
(
x
)
=
3
x
3
−
5
x
2
−
47
x
−
15
Explanation:
If the zero is c, the factor is (x-c).
So for zeros of
−
3
,
−
1
3
,
5
, the factors are
(
x
+
3
)
(
x
+
1
3
)
(
x
−
5
)
Let's take a look at the factor
(
x
+
1
3
)
. Using the factor in this form will not result in integer coefficients because
1
3
is not an integer.
Move the
3
in front of the x and leave the
1
in place:
(
3
x
+
1
)
.
When set equal to zero and solved, both
(
x
+
1
3
)
=
0
and
(
3
x
+
1
)
=
0
result in
x
=
−
1
3
.
f
(
x
)
=
(
x
+
3
)
(
3
x
+
1
)
(
x
−
5
)
Multiply the first two factors.
f
(
x
)
=
(
3
x
2
+
10
x
+
3
)
(
x
−
5
)
Multiply/distribute again.
f
(
x
)
=
3
x
3
+
10
x
2
+
3
x
−
15
x
2
−
50
x
−
15
Combine like terms.
f
(
x
)
=
3
x
3
−
5
x
2
−
47
x
−
15
Answer:
14
Step-by-step explanation:
56 divided by 7 = 8
14 divided by 7 = 2
hinting at 8/2
Answer:
P1= -2/3
P2= -10/3
Step-by-step explanation:
take the sq rt of both sides and use both + and - roots
3P+6=4
3P+6=-4
subtract 6 from both sides for each one
3P=-2
P=-2/3
3P=-10
P= -10/3
Answer:
0 of the linear function is the start of the line your answer would be the end of the line